Problematika Pembelajaran Menulis Teks Cerpen Kelas VII di SMP Negeri 5 Malang - Azza Aulia Ramadhani (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2020)
This study aims to obtain objective descriptions related to the problematics of learning to write short stories in grade VII at SMP Negeri 5 Malang and solutions that can be applied to overcome these problems. This study used a qualitative design with a descriptive approach. The research data is in the form of observations that have been made which are then analyzed. Based on the results of the analysis, it was obtained the conclusion of the problems that exist in the learning process of writing short stories text for class VII at SMP Negeri 5 Malang along with the solutions given to the teacher to overcome these problems.